Advanced Diagnosis of Glioma by Using Emerging Magnetic Resonance Sequences - Wei, Ruo-Lun; Wei, Xin-Ting (Frontiers in Oncology, 2021)
Glioma, the most common primary brain tumor in adults, can be difficult to discern radiologically from other brain lesions, which affects surgical planning and follow-up treatment. Recent advances in the MR imaging demonstrate the preoperative diagnosis of glioma have stepped in to molecular and algorithm assisted level. Specifically, the histologic-based glioma classification is composed of multiple different molecular subtypes with distinct behavior, prognosis and response to therapy, and now each aspect of them can be assessed by corresponding emerging MR sequence like amide proton transfer-weighted MRI, inflow vascular-space-occupancy MRI and radiomic algorithm. As a result of these novel progress, the clinical practice of glioma has been updated. Accurate diagnosis of glioma at molecular level can be achieved ahead of operation to formulate a thorough plan including surgery radical level, shorten length of stay, flexible follow-up plan, timely therapy response feedback and eventually benefit patient individually.